O23 Clinical and laboratory aspects of condylomata lata lesions of syphilis. (16th June 2022) - Towns, Janet; Denham, Ian; ,; Graves, Stephen; Fairley, Christopher; Williamson, Deborah; Azzato, Francesca; Chen, Marcus
Abstract : Objectives Condylomata lata (CL) are a distinctive syphilitic lesion. Our aim was to determine clinical and laboratory characteristics of CL by determining: (1) the most closely aligned stage of syphilis, based on the rapid plasma reagin (RPR) titre; (2) symptom duration; and (3) Treponema pallidum polymerase chain reaction (PCR) cycle threshold (CT) values, as an indicator of organism load. Methods: This retrospective study was of patients with T. pallidum PCR-positive CL lesions, attending a public STI clinic. Syphilis serology was undertaken and RPR titres compared between CL, primary and secondary syphilis cases. Results: 51 cases with T. pallidum PCR-positive CL were included. 41 cases were in men, 40 of whom were men who have sex with men (MSM), and 10 in women. Twelve/51 (24%) cases were in HIV-positive MSM. Thirty-three/51 (65%) had other mucocutaneous signs of secondary syphilis; 18 (35%) had no other signs of secondary syphilis. The median RPR titre among 51 CL cases was 1:128, compared to primary syphilis (1:4), and secondary syphilis (1:128). The median lesion duration was 24 (IQR 10 - 60) days, with no significant difference between those with and without other signs of secondary syphilis (p = 0.75). Median CT values for CL - and primary syphilis - were significantly lower than for other secondary syphilis lesion types, indicating higher T. pallidum loads for CL and primary lesions compared to other secondary syphilis lesion types. Discussion: These findings support CL as lesions occurring during secondary syphilis, which are likely to be highly infectious.